VD_FINDINFO Arrêt / 2010 / 1303 vom 12. August 2010 - VD Tribunal cantonal (2010)
INTENTION, ACCIDENT, SUICIDE, CAPACITÉ DE DISCERNEMENT, ASSISTANCE JUDICIAIRE | 16 CC, 37 al. 1 LAA, 6 al. 1 LAA, 37 al. 4 LPGA, 48 OLAA